Proton beam therapy in the management of skull base chordomas: systematic review of indications, outcomes, and implications for neurosurgeons. (3rd July 2016) - Matloob, Samir A.; Nasir, Haleema A.; Choi, David
Abstract: Background: Chordomas are rare tumours affecting the skull base. There is currently no clear consensus on the post-surgical radiation treatments that should be used after maximal tumour resection. However, high-dose proton beam therapy is an accepted option for post-operative radiotherapy to maximise local control, and in the UK, National Health Service approval for funding abroad is granted for specific patient criteria. Objectives: To review the indications and efficacy of proton beam therapy in the management of skull base chordomas. The primary outcome measure for review was the efficacy of proton beam therapy in the prevention of local occurrence. Methods: A systematic review of English and non-English articles using MEDLINE (1946–present) and EMBASE (1974–present) databases was performed. Additional studies were reviewed when referenced in other studies and not available on these databases. Search terms included chordoma or chordomas. The PRISMA guidelines were followed for reporting our findings as a systematic review. Results: A total of 76 articles met the inclusion and exclusion criteria for this review. Limitations included the lack of documentation of the extent of primary surgery, tumour size, and lack of standardised outcome measures. Level IIb/III evidence suggests proton beam therapy given post operatively for skull base chordomas results in better survival with less damage to surrounding tissue. Conclusions: Proton beam therapy is a grade B/C recommended treatment modality for post-operative radiation therapy to skull base chordomas. In comparison to other treatment modalities long-term local control and survival is probably improved with proton beam therapy. Further, studies are required to directly compare proton beam therapy to other treatment modalities in selected patients.